ANALISIS POSITIONING NOTEBOOK ACER DI DAERAH JAKARTA SELATAN (Perceptual Mapping Acer dengan notebook pesaing) - Hartanto (2013)
Positioning on the nature-oriented nature diferensasi. They defined it as a creative effort to create a unique and superior position for a brand in the minds of target customers so that the brand can stand out among the crowd of similar brands that are flooding the market. The analysis technique used in this study is a multivariate analysis technique. The multivariate analysis of related statistical methods jointly conducted an analysis of more than two variables on each product. To determine the similarity between the products can be done with the Multi Dimensional Scaling (MDS) and Correspondence Analysis (CA) to determine the advantages of each variable for each produk.alat analysis is used and overlap, because MDS and CA are both generate output map perceptual (perceptual map ) that describes the position of notebook Acer and its competitors. Through MDS and CA are expected to obtain information about the positioning of the Acer notebook, as well as the attributes of excellence preferences Acer notebook. This information will be used as a basis in determining marketing strategies that can be applied to notebook Acer to strengthen the positioning based on the attributes possessed as a notebook.